2023
DOI: 10.2147/dddt.s393995
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mechanism of Action of Schisandra chinensis Combined with Coenzyme Q10 in the Treatment of Heart Failure Based on PI3K-AKT Pathway

Abstract: To study the active components, drug targets and mechanism of Schisandra chinensis (S.chinensis) combined with coenzyme Q10 (CQ10) in the treatment of heart failure (HF). Methods: Network pharmacology combined with the gene expression omnibus chip method to analyze the main pathways by which S.chinensis combined with CQ10 functioned to treat heart failure. Subsequently, the biological activities of the major pathway key proteins and their corresponding compounds were verified by molecular docking techniques. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Further exploring its anti‐atherosclerotic molecular mechanism, it was hypothesized that Sch C may alleviate arterial inflammation by inhibiting the phosphorylation and degradation of IκB α [68] . Network pharmacology combined with experimental validation showed that Sch C may be one of the active components in the inhibition of heart failure, and its combination with CQ10 could effectively improve cardiac coefficients and reduce serum levels of IL‐1 β and TNF‐ α in rats with heart failure, as well as reduce apoptosis of cardiomyocytes, increase the expression of Bcl‐2, and reduce p‐AKT/AKT, P65, and Bax in heart tissue expression in heart tissue [69] …”
Section: Bioactivitymentioning
confidence: 99%
“…Further exploring its anti‐atherosclerotic molecular mechanism, it was hypothesized that Sch C may alleviate arterial inflammation by inhibiting the phosphorylation and degradation of IκB α [68] . Network pharmacology combined with experimental validation showed that Sch C may be one of the active components in the inhibition of heart failure, and its combination with CQ10 could effectively improve cardiac coefficients and reduce serum levels of IL‐1 β and TNF‐ α in rats with heart failure, as well as reduce apoptosis of cardiomyocytes, increase the expression of Bcl‐2, and reduce p‐AKT/AKT, P65, and Bax in heart tissue expression in heart tissue [69] …”
Section: Bioactivitymentioning
confidence: 99%
“…Research shows that schizandra juice, especially in combination with coenzyme Q10, helps reduce the area of myocardial fibrosis in patients with heart failure, improves heart function [15] and protects against the development of cardiovascular diseases. [16]…”
Section: Effective In Treating Heart Failurementioning
confidence: 99%